PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA KOMIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP - Rina Kusumahati; Usep Kosasih (UJMES (Uninus Journal of Mathematics Education and Science), 2016)
The research based on the low mathematical creative thinking ability. To overcome this problem. Student Teams AchievementDivision (STAD) which is assisted by comic media, can be an alternative cooperative learning model. This research examinedthe increasing problem of creative mathematical thinking ability after receive STAD cooperative learning model. This researchaims to figure out students response towards mathematic course. This research was a quasi-experimental research design withNon-Equivalent Control Group Design using purposive sampling technique. The population in this research was the seventhgrade of SMPN 18 Bandung in 2013/2014. The sample of this research was the students class VII-3 and VII-5. Aninstrument used in the study was ability of mathematical creative thinking test. Data acquired is analyzed both quantitativeand qualitative. Moreover, the data of pre-test, post-test, and n-gain are calculated by SPSS 21 for Windows. The resultshowed that, the increasing of students mathematical creative thinking ability who receive STAD cooperative learning modelassisted by comic media is better than students who receive conventional learning. Meanwhile, based on questionnaire analysis,conclusion can be drawn that students respond positively towards Mathematics course after using STAD cooperative learningmodel assisted by comic media.